The technique of foreshadowing in the novel "Graves of the Living" by Diaa El-Din Khalifa (A study extracted from a master's thesis) - محمد, سایا صالح; Masti, Prof. Dr. Nian Noshirvan Fouad (Sulaimani Journal for Humanities, 2026)
This research examines the mechanism of "time foreshadowing" as an element of temporal structure in the narrative text, and as one of the fundamental components that constitute science fiction novels, particularly dystopian novels, which possess a futuristic character, transcending the boundaries of natural time and breaking its linearity. In this context, "time foreshadowing" is not merely a narrative technique; it transcends this, representing an aesthetic and intellectual tool that contributes to establishing the dystopian dimension of the text. It, in turn, carries a critical vision of reality through the reshaping of time as a space in crisis. The narrative reflects the distortion of society and the alienation of humanity, along with the fragmentation, fear, and loss of meaning that afflict its consciousness, so that time itself becomes an expression of the human crisis experienced by the characters within the fictional world.
Keywords: Anticipating time; science fiction; dystopia; graveyards of the living; Diaa ElDin Khalifa